COVID-19 AND VIRAL PNEUMONIA: SIMILARITIES AND DIFFERENCES - Nurulla Qurbonov Nurulla Qo'ziboy o'g'li (Scholar Express Journals, 2025)
COVID-19, caused by the novel coronavirus SARS-CoV-2, has reshaped global healthcare systems, drawing attention to viral pneumonia as a severe respiratory complication. While both COVID-19 and traditional viral pneumonia share similar symptoms and respiratory manifestations, they differ in etiology, pathophysiology, clinical progression, and management strategies. This article aims to delineate the similarities and differences between COVID-19-associated pneumonia and pneumonia caused by other respiratory viruses, including Influenza and RSV (respiratory syncytial virus). Through an extensive review of recent literature, this study discusses the underlying mechanisms, diagnostic tools, and treatment approaches. A comparative analysis reveals unique aspects of COVID-19, such as its propensity to cause systemic complications and long-term sequelae, providing valuable insights into improving clinical outcomes and preparedness for future pandemics
Keywords: COVID-19; SARS-CoV-2; viral pneumonia; respiratory infections